Faculty-led small group learning versus didactics presentation in a genetics course in medical biochemistry a comparative study - Velayo-Pilones, Elvira (2003)
In recent years, the traditional didactic format has been under critical review as a method of teaching because of its inhibitory effects to developing analytical and investigative skills important among medical students. Various curricular innovations have thus been proposed with renewed vigor to address this particular dilemma. Small group learning is one such innovation which aims to promote a more active and dynamic role for the medical student in terms of knowledge, attitude and skills acquisition thereby empowering him to further advance self-education. In a small group interaction, students gain a more profound understanding of information and obtain the opportunity of cooperatively working in a group and develop essential group skills. The use of SGL in Philippine medical education, however, has not been thoroughly studies and its potential benefits still not yet sufficiently validated. This research paper compared the performance of first year medical students in a genetics course taught using small group learning and didactic presentation. In a randomized pretest, posttest research design, all first year medical students were randomly assigned to either one of the two instructional settings. Outcome measures included immediate performance in pretest and posttest and feedback from attitude toward learning assessment questionnaires In terms of gains in actual knowledge as evaluated in a multiple-choice type comprehensive examination, statistical comparison using t-test for unmatched pairs in the post test performance of students in an SGL format versus that of didactics presentation showed no significant difference (p=0.380). Scores in the post- test examination, however were significantly improved in both SGL (p<0.001) and didactics (p<0.001) groups. Post test ratings in the attitudinal rating scale were significantly improved for both groups on Wilcoxon Signed Rank Test (p<0.001). The responses also showed that an SGL experience had a propensity to influence attitudes relating to information processing and self-directed/independent learning. An SGL environment was found to positively reinforce a student's confidence to tackle a subject matter usually by means of self-study and/or collaboration with fellow students (Wilcoxon p=0.007), capacity to integrate previous learning to present goals (Wilcoxon p=0.012), motivation to study (Wilcoxon p=0.035), confidence of their ability to pass evaluation tools on the basis of what they know and understand (Wilcoxon p=0.021) and a healthy appreciation of feedback or reinforcement phase (Wilcoxon p=0.005). The preliminary results show that type of teaching-learning process (whether didactics or SGL) did not affect the performance of students in a competency-based comprehensive examination in genetics. However, any institutional initiative towards a dramatic curricular shift from a conventional didactics-based learning environment should be substantiated by a more comprehensive study.
Thesis (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Small groups; Genetics -- Study and teaching